Visualization of intraocular foreign bodies in the projection of the ciliary body by transpalpebral near-infrared transillumination (Ukrainian Journal of Ophthalmology, 2025)
Background: Despite advances in intraocular foreign body (IOFB) diagnosis, detecting IOFB is a challenge for the ocular traumatologist.Purpose: To assess the potential of near-infrared transpalpebral transillumination (NIR TPT) for visualization of IOFB in the projection of the ciliary body to the sclera.Materials and Methods: Ten patients (10 eyes) with penetrating globe injuries associated with IOFB were under observation. All patients underwent an X-ray examination with frontal and lateral projections (both with and without using the Komberg-Baltin prosthesis), ultrasound scanning of the anterior eye and posterior eye; ultrasound distant perimetry; metal detector examination; and NIR TPT.Results: In all patients, NIR TPT visualized scleral shadows of the ciliary body pars plicata and pars plana as well as the IOFB shadow. The IOFB was localized in relation to ciliary body structures in all cases.Conclusion: NIR TPT enables non-invasive visualization of IOFBs in the anterior segment, as well as localization of these IOFBs in relation to ciliary body structures in patients with penetrating globe injury.
Keywords: penetrating globe injury; intraocular foreign body; infrared radiation; transillumination